Pengelolaan Konflik Horizontal di Kampung Harapan Jaya Kabupaten Berau Berbasis Pendekatan Formal dan Informal - Annisa Kirana Andaneswari; Adrian Adrian; Melany Putri Bella Cristina (Department of International Relations, University of Mataram, 2021)
This research uses a qualitative methodology by using inductive logic which tries to present new alternative thinking. This research explains a conflict management in Kampung Harapan Jaya, Berau Regency, East Kalimantan. Through discourse analysis, the study seeks to analyze the management of conflicts formed through both formal and informal approaches. The purpose of this research is to contribute to the theoretical realm while making new findings that can be translated into an alternative policy for the government in the context of conflict management in plural areas. The main finding of this research shows that the conflict in Kampung Harapan Jaya is managed through three approaches, namely the figure approach, the region governance approach, and the socio-economic interaction approach among the local community. The region’s governance approach leads to a negative peace situation. Meanwhile, the approach the informal interaction through socio-economic activities based on the local wisdom act has greater potential in creating positive peace situations. This research is important as a contribution to the issue of peace studies based on best practice research